Application of Landsat images to seagrass areal cover change analysis for Lawas, Terengganu and Kelantan of Malaysia. (1st November 2015) - Hossain, M.S.; Bujang, J.S.; Zakaria, M.H.; Hashim, M.
Abstract: Seagrass mapping and monitoring using remote sensing has been established using various imageries and mapping methods, ranging from complex optical modeling to manual interpretations. Few attempts have been made to find relations between spatiotemporal changes within seagrass habitats and their surrounding environment in the mapping efforts. In this study, issues of spatiotemporal changes in seagrass habitat including water quality, and causes and processes of seagrass degradation were addressed through assessing the ability of integrated manual enhancement and seed pixel growing techniques on multi-date Landsat images for mapping and monitoring seagrass resources. This integrated approach was tested on a total of forty-nine Landsat 5, 7 and 8 images of the seagrass meadow spatial distribution and cover change analysis for Punag-Sari estuary (Lawas), Pengkalan Nangka (Kelantan) lagoon, and Paka (Terengganu) lagoon of Malaysia. The resulted maps demonstrated the ability of Landsat images for producing spatially extensive maps and allowed quantitative estimation of seagrass coverage, accretion/erosion, and describe changes in noticeable areas. The findings indicated that a noticeable loss of seagrass habitats at varying magnitude occurred between 2000 and 2014 for Punang-Sari, between 1998 and 2014 for Pegkalan Nangka, and between 1988 and 2014 for Paka. The natural event mainly sand shifting was the main cause of seagrass habitat loss for Punang-Sari Lawas. Coastline change was identified as the most significant factor that caused seagrass spatial cover loss of the Pengkalan Nangka lagoon. The seagrass meadows of Pengkalan Nangka and Paka were greatly affected by natural events including floods, and local human-induced interferences such as dredging, and sand mining. The mapping approach and the map products presented in this paper will be a useful information source for the coastal management agencies involved in monitoring and management programs. Highlights: Landsat image analysis provides spatiotemporal dynamics of seagrass meadows. Image enhancement was combined with pixel-growing algorithm for image analysis. Seagrass cover changes were presented for the east and west coasts of Malaysia. Land use and cover change dynamics influencing seagrass cover is discussed.